An affordable, water-based, community condensation particle counter - Hering, Susanne V.; Amanatidis, Stavros; Eiguren-Fernandez, Arantzazu; Lewis, Gregory S.; Spielman, Steven R.; Pariseau, David (Aerosol science and technology, 2025)
A "Community Condensation Particle Counter" (cCPC) has been developed to provide an affordable monitor of airborne particle number concentrations. The cCPC is an expansion-type condensation particle counter that incorporates single particle counting to yield a direct measurement of number concentration. Particle number concentrations are derived from the detection of individual droplets exiting the cell during the expansion, combined with the pressure readings and the physical volume of the particle cell. Modeling and experiment confirm detection of particles as small as 4 nm, with >95% detection above 20 nm. For 12 d of ambient sampling two collocated cCPCs exhibit a pooled standard deviation of 3.5%. Comparison to a pair of benchtop instruments (ADI MAGIC CPCs) yields a correlation of R 2 = 0.98 and a regression slope of 1.1. Laboratory studies at concentrations higher than 3 × 10 4 cm −3 for both sulfate and dioctyl sebacate show equally reduced response when compared to a versatile water CPC, but this was not observed in ambient aerosol sampling. Further research will be needed to resolve this discrepancy.